THE ROLE OF IRONY IN LITERATURE AND COMMUNICATION - Ortiqova Nozima (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract. This article explores irony's impact on literature and communication. Verbal, situational, and irony of fate each offer unique insights into human experience. Irony enables nuanced critique, fosters engagement, and enhances cultural commentary. Embracing irony enriches storytelling, challenging norms, and stimulating deeper understanding.